Towards Lean Manufacturing in Developing Countries: Research Gaps and Directions in Tanzania - Sinkamba, Francis; Matindana, Juma M.; Mgwatu, Mussa (Tanzania Journal of Engineering and Technology, 2025)
In the current knowledge-driven economy, many industries across the globe are forced to adopt manufacturing technologies such as lean manufacturing to remain competitive in the globalized world. Despite the increase in lean manufacturing implementations, the adoption rate in Tanzania is very low and estimated to be 8 percent. Likewise, the sustainability of lean manufacturing tools and practices is still questionable, which shows the need to develop lean maturity models. To date, several lean maturity models have been developed but there is a lack of maturity models that consider different levels of manufacturing industries. The study presented in this paper focused on the pre-implementation, implementation, and post-implementation phases of lean manufacturing. To achieve this aim, a systematic literature review and social network analysis using VOS viewer 1.6.18 were conducted. The literature was obtained from four academic databases: Emerald, Elsevier, Springer, and Taylor and Francis. The search covered the period from 2010 to 2022. Of the 100 publications analyzed on lean manufacturing, only 1 percent is from low-income developing countries and 5 percent of publications from Africa. The study has identified that there are few numbers of research publications on lean manufacturing in Africa and low and lower-middle-income developing countries in general, as a result there is a low rate of implementation of lean manufacturing in low and lower-middle-income developing countries. It is recommended that more studies on the drivers and barriers, critical success factors, and lean assessment be conducted in developing countries.